Some regulation of agricultural land use and regulatory arrangements - P, Sodgerel; A, Narantuya (Mongolian Journal of Agricultural Sciences, 2018)
Legislation on cropping is to regulate the relations pertaining to the cultivation, establishment of crop areas, rational use of farms, protection of soil and improvement of crop and intensive livestock production. However, there is a lack of enforcement and lead to disagree with crop and herder farmers. In this study, the consequences of enforcing the law were to suggest a scientifically-oriented approach. According to the results of the survey, crop farms in Darkhan-Uul aimag are crowded in one place and over 200 hectares are expected to undermine the stability of the landscape. Some provisions for the implementation of the Law on Crops are: 24.2 and 24.4 tend to conflict with herders and farmers. Consequently, ecologically and adapted land management measures are essential.